Imperial Riding School in Vienna - Lemaitre, Augustin François, 1797-1870 (engraver):::Creator::::::::::::; Le Bas, Philippe, 1794-1860 (author):::Contributor:::::::::::: (Paris; Didot frères; France)
Color engraving of the imperial riding school in Vienna